Early worsening of diabetic retinopathy after simultaneous pancreas and kidney transplantation—Myth or reality?. Issue 10 (13th May 2020) - Voglová, Barbora; Hladíková, Zuzana; Nemétová, Lenka; Zahradnická, Martina; Kesslerová, Kateřina; Sosna, Tomáš; Lipár, Květoslav; Kožnarová, Radomíra; Girman, Peter; Saudek, František
Abstract : Early worsening of diabetic retinopathy due to sudden glucose normalization is a feared complication of pancreas transplantation; however, its rate or severity has not been studied prospectively. We followed up 43 pancreas and kidney recipients for a composite endpoint comprising new need for laser therapy, newly diagnosed proliferation, macular edema, visual acuity worsening, and blindness over 12 months. Although 37% of patients met this primary endpoint, its severity was rather low. Mean central retinal thickness and proportion of patients with subclinical macular edema increased significantly, with spontaneous resolution in half of them. Visual acuity did not change. There was no significant difference in the absolute glycated hemoglobin (HbA1c) drop, age, and diabetes duration between the patients who met and those who did not meet the primary endpoint, but a higher proportion of patients with worsening had a recent history of laser treatment. Retinopathy remained stable in 62.8% of patients. In 26%, the visual acuity significantly improved. Although retinopathy worsening was documented in more than one‐third of patients, its evolution was not related to the magnitude of metabolic change; rather, it corresponded to the expected natural course of retinopathy. Nonetheless, comprehensive ophthalmologic care should be a substantial component of the recipient management. Abstract : In the first year after simultaneous pancreas–kidney transplantation, the progression of diabetic retinopathy that occurs in approximately one‐third of recipients shows association with pretransplant retinopathy state rather than the abrupt change in glucose control.